Cover Picture: Conversion of Ammonia to Hydrazine Induced by High‐Frequency Ultrasound (Angew. Chem. Int. Ed. 48/2021). Issue 48 (14th October 2021) - Humblot, Anaelle; Grimaud, Laurie; Allavena, Audrey; Amaniampong, Prince N.; De Oliveira Vigier, Karine; Chave, Tony; Streiff, Stéphane; Jérôme, François
Abstract : Ammonia has been converted into hydrazine, a chemical of utmost importance for organic synthesis and energy purposes. In their Communication on page 25230, François Jérôme et al. report that cavitation bubbles, created by ultrasonic irradiation of aqueous ammonia at a high frequency, act as microreactors to activate and convert ammonia into hydrazine at the gas–liquid interface. Maintaining the aqueous solution close to 30 °C prevents the degradation of in situ produced hydrazine.